INTERACTIONAL UNFOLDING OF VOCABULARY EXPLANATIONS IN MEANING AND FLUENCY CONTEXTS - Elif Taşkın (Informascope, 2017)
In the field of foreign and second language education, there is great deal of research on vocabulary teaching and learning. However, there is relatively limited research dealing with the vocabulary explanations during ongoing classroom interaction. This article aims to provide vocabulary explanation sequences in meaning and fluency contexts (Seedhouse, 2004). To this end, a foreign language education classroom including 13 students was recorded for a classroom hour, and the interaction in the classroom was transcribed. The classroom interactions were analyzed by using conversation analysis methodology, and vocabulary explanation examples were described in detail. As a result of the analysis, two vocabulary explanation sequences are provided in meaning and fluency contexts based on the students' responses. Results show that when the students display understanding in their native language, the teacher asks follow-up questions before closing the turn; however, when they display understanding in the target language, the teacher closes the turn without asking further questions. Keywords: conversation analysis, vocabulary explanation, meaning and fluency contexts, classroom interaction.